How pyroptosis contributes to inflammation and fibroblast-macrophage cross-talk in rheumatoid arthritis - Demarco, B; Danielli, S; Fischer, FA; Bezbradica, JS (MDPI, 2022)
About thirty years ago, a new form of pro-inflammatory lytic cell death was observed and termed pyroptosis. Only in 2015, gasdermins were defined as molecules that create pores at the plasma membrane and drive pyroptosis. Today, we know that gasdermin-mediated death is an important antimicrobial defence mechanism in bacteria, yeast and mammals as it destroys the intracellular niche for pathogen replication. However, excessive and uncontrolled cell death also contributes to immunopathology in several chronic inflammatory diseases, including arthritis. In this review, we discuss recent findings where pyroptosis contributes to tissue damage and inflammation with a main focus on injury-induced and autoimmune arthritis. We also review novel functions and regulatory mechanisms of the pyroptotic executors gasdermins. Finally, we discuss possible models of how pyroptosis may contribute to the cross-talk between fibroblast and macrophages, and also how this cross-talk may regulate inflammation by modulating inflammasome activation and pyroptosis induction.